The use of cardiovascular magnetic resonance for the assessment of left ventricular hypertrophy - AJM Lewis; OJ Rider (AME Publishing Company, 2020)
Cardiovascular magnetic resonance (CMR) is a powerful tool to assess and diagnose the cause of left ventricular hypertrophy (LVH). This review provides an overview of the typical CMR findings in the various causes of LVH, focusing mainly on late gadolinium enhancement (LGE) imaging. It will also cover the more novel techniques of T1 mapping, extracellular volume (ECV) fraction estimation and diffusion tensor imaging (DTI) and their role in the imaging assessment of LVH.